Comparison of conventional and fast pyrolysis for the production of Jatropha curcas bio-oil - Seyed, Amirmostafa Jourabchi (Elsevier, 2016)
The objectives of this study are to parametrically investigate and optimise bio-oil production from a fast pyrolysis process for comparison with conventional pyrolysis using a tubular furnace, and to characterise the physicochemical properties of optimum bio-oils from both processes. Although rapid heating fast pyrolysis reduces the bio-oil yield, the gross calorific value (GCV) and water content of bio-oil improves. At optimum reaction temperature of 747.15 K and N2 linear velocity of 0.0078 cm/s for fast pyrolysis, 40.93 wt% of biomass was converted into bio-oil with a GCV of 16.92 MJ/kg, water content of 28.02 wt% and pH of 7.01. Physicochemical properties of Conventional Pyrolysis Dehydrated Bio-Oil (CPDB) and Fast Pyrolysis Dehydrated Bio-Oil (FPDB) were tested against ASTM D7554-10. By reducing the sulphur contents, both CPDB and FPDB can be used as burner fuel. CPDB BO10 and FPDB BO10 (10% of CPDB and FPDB emulsified in 90% diesel, respectively) were tested for their physicochemical properties against EN590 and ASTM D6751-01 standards for diesel and biodiesel, respectively. Should the sulphur and water content of CPDB BO10 and FPDB BO10 be removed, they can be commercially used as diesel fuel in diesel engines because all other properties meet the EN590 standard.